Helios, a T cell-restricted Ikaros family member that quantitatively associates with Ikaros at centromeric heterochromatin - Hahm, Kyungmin (Cold Spring Harbor Laboratory Press, 1998)
The Ikaros gene encodes multiple protein isoforms that contribute critical functions during the development of lymphocytes and other hematopoietic cell types. The intracellular functions of Ikaros are not known, although recent studies have shown that Ikaros proteins colocalize with inactive genes and centromeric heterochromatin. In this study, Ikaros proteins were found to be components of highly stable complexes. The complexes from an immature T cell line were purified, revealing associated proteins of 70 and 30 kD. The p70 gene, named Helios, encodes two protein isoforms with zinc finger domains exhibiting considerable homology to those within Ikaros proteins. Helios and Ikaros recognize similar DNA sequences and, when overexpressed, Helios associates indiscriminately with the various Ikaros isoforms. Although Ikaros is present in most hematopoietic cells, Helios was found primarily in T cells. The relevance of the Ikaros–Helios interaction in T cells is supported by the quantitative association of Helios with a fraction of the Ikaros. Interestingly, the Ikaros–Helios complexes localize to the centromeric regions of T cell nuclei, similar to the Ikaros localization previously observed in B cells. Unlike the B cell results, however, only a fraction of the Ikaros, presumably the fraction associated with Helios, exhibited centromeric localization in T cells. These results establish immunoaffinity chromatography as a useful method for identifying Ikaros partners and suggest that Helios is a limiting regulatory subunit for Ikaros within centromeric heterochromatin.